ELECTROCATALYTIC ACTIVITY OF LiNiPO4 AND THE COPPER DOPED ANALOGUES TOWARDS OXYGEN REDUCTION - Janjua, N. K.; Mumtaz, M.; Yaqub, A.; Sabahat, S.; Mujtaba, A. (The Nucleus, 2014)
Olivine type single phase LiNi(1-x)CuxPO4 (0 < x < 0.99) samples were successfully synthesized by non-aqueous sol-gel method followed by microwave (MW) annealing.. The phase purity, lattice parameters and morphology was confirmed by FTIR, XRD and SEM studies. X-Ray diffraction patterns of both the parent LiNiPO4 (LNP) and doped analogues were similar. Vegard law signifies a linear relation between lattice parameter and dopant concentration. Resultant change (either expansion or shrinkage) in lattice parameters as a result of doping means that effective doping is done showed effective doping by following the Vegard’s law. Both LNP and its doped analogues were found to be electrocatalysts towards oxygen reduction which is apparently due to nanosized particles as obtained via MW annealing.